Зміна позову в цивільному судочинстві : автореф. дис. - Пуль, С. І.; Pul, S. I.; Пуль, С. И. (Харків, 2018)
Дисертація присв’ячена комплексному дослідженню теоретичних та практичних проблем зміни позову в цивільному судочинстві. В роботі доведено, що позов як процесуальний засіб захисту порушених, невизнаних або оспорюваних прав, свобод чи інтересів є процесуальною категорію, в якій матеріально-правовий характер вимоги особи, права, свободи чи інтереси якої ймовірно порушені, втрачає своє значення, трансформуючись у процесуально-правову вимогу до суду про застосування визначеного законом або договором способу захисту. З урахуванням його процесуально-правової природи визначено поняття позову як процесуального засобу, сутністю якого євимога заінтересованої особи до суду про захист свого або чужого права або охоронюваного законом інтересу у спосіб, передбачений законом або договором, або в інший ефективний спосіб, який не суперечить законодавству, з підстав, визначених обставинами справи та вимогами закону. Внутрішня структура позову обумовлена його процесуальною сутністю та включає два елементи: предмет і підстави. Здійснено класифікацію форм зміни позову, яка впливає на його зміст і здійснюється шляхом якісної та кількісної зміни його елементів. Аналіз судової практики підтверджує можливість і необхідність одночасної зміни предмета і підстав позову для здійснення ефективного захисту порушеного суб’єктивного права чи охоронюваного законом інтересу.

The author of the paper has proved that a suit as a procedural mean of protecting violated, unrecognized or disputed rights, freedoms and interests is a procedural category, where the material and legal nature of a person’s request, whose rights, freedoms or interests are probably violated, loses its meaning, being transformed into procedural and legal demand to the court for the application of a method of protection specified by the law or contract. Taking into account its procedural and legal nature the author has determined the concept of a suit as a procedural tool, the essence of which is the requirement to the court by the adverse claimant for the protection of his or someone else’s rights or legally protected interest in the manner prescribed by the law or contract or in other effective manner that does not contradict to the legislation, on the grounds determined by the circumstances of the case and the requirements of the law. The internal structure of a suit is due to its procedural nature and includes two elements: the subject matter and grounds. The subject matter of a suit is a legal requirement directed at the protection of rights or interests: a method of protection, which is defined by the law or contract. The grounds of a suit are circumstances relied upon by the claimant to substantiate his claims and which confirm the origin, change, cessation of material legal relations, violation of the right or interest. The author has carried out the classification of forms of changing a suit, which affects its content and realized through qualitative and quantitative change in its elements. Replacement of elements is carried out by replacing the method of protection or the circumstances, which are the grounds for the provided demand; addition of the subject matter and (or) the grounds of a suit is an addition to one or more methods of protecting the right and (or) circumstances; the clarification is the exclusion of certain methods of protection or circumstances or the quantitative change within the method of protection through the reduction or increase of the object of a dispute. Admissibility of replacement of a suit’s elements is due to the fact that the methods of protection established by the law or contract, either does not contradict to it or circumstances, which bind the law with the emergence, change or termination of disputable legal relations, are alternatively specified. Changing the subject matter of a suit in the form of clarification is a change within the originally claimed method of judicial protection that does not impact on the content of a suit in the whole and is combined with the specification of appropriate grounds. Analysis of judicial practice confirms the possibility and necessity of simultaneous change in the subject matter and grounds of a suit for the implementation of effective protection of the violated subjective right or an interest protected by the law. On the basis of the obtained conclusions, the author has formulated recommendations for amending the Civil Procedural Code of Ukraine. The scientific novelty of the obtained results is that the author within the framework of a comprehensive research has carried out a systematic theoretical and practical analysis of the modern problems of changing a suit within civil legal proceedings. The obtained results have found practical application in the development of theoretical and legal provisions for the improvement of the legal institution of the suit, in particular, the legal grounds and the procedure for replacing, clarifying and supplementing a suit, to be more precise, in the research area, in law-making and law-enforcement activities, as well as in the educational process.

Диссертация посвящена комплексному иследованию теоретических и практических проблем изменения иска в гражданском судопроизводстве. В работе доказано, что иск как процессуальное средство защиты нарушенных, непризнанных или оспариваемых прав, свобод или интересов является процессуальной категорией, в которой материально-правовой характер требования лица, права, свободы или интересы которой вероятно нарушены, теряет свое значение, трансформируясь в процессуально правовое требование в суд о применении определенного законом или договором способа защиты. С учетом его процессуально-правовой природы определено понятие иска как процессуального средства, сущностью которого является требование заинтересованного лица в суд о защите своего или чужого права или охраняемого законом интереса способом, предусмотренным законом или договором, или в другой эффективный способ, который не противоречит законодательству, по основаниям, определенным обстоятельствам дела и требованиям закона. Внутренняя структура иска обусловлена его процессуальной сущностью и включает два элемента: предмет и основания. Осуществлена классификация форм изменения иска, которая влияет на его содержание и осуществляется путем качественной и количественной изменений его элементов. Анализ судебной практики подтверждает возможность и необходимость одновременного изменения предмета и оснований иска для осуществления эффективной защиты нарушенного субъективного права или охраняемого законом интереса.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук (доктора філософії)
Changing a Suit within Civil Legal Proceedings
Пуль, С. І. Зміна позову в цивільному судочинстві : автореф. дис. ... канд. юрид. наук ( доктора філософії) : 12.00.03 / С. І. Пуль; МВС України, Харк. нац. ун-т внутр. справ. - Харків, 2018. - 24 с.
Keywords: Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; Україна. Ukraine. Украина; 12.00.03; цивільне судочинство; цивільний процес; позов; зміна позову; гражданское судопроизводство; гражданский процесс; иск; изменение иска; lawsuit; civil legal proceedings; позивач; истец; claimant